PENGEMBANGAN SOLAR DRYER DOME UNTUK PENINGKATAN KUALITAS PRODUKSI KOPI - Kusmiyati Kusmiyati; Abu Salam; Juli Ratnawati (Politeknik Negeri Sriwijaya, 2021)
Community service activities with SME Omah Kopi Ngemplak Banyuanyar Village were carried out to increase the capacity and quality of production of ground coffee, green coffee beans, and roasted coffee beans. From the observations of the Service Team to partners, there were two problems. The first problem: Omah Kopi Ngemplak produces coffee using the traditional drying method which relies on sunlight. Drying is one of the most important coffee processing processes because it affects the quality of the coffee beans produced. This drying process takes a long time and has the potential to rot in the rainy season so that farmers' performance is hampered and the quality of coffee beans decreases. The second problem is the limited marketing of coffee where farmers only sell coffee to middlemen and stalls, in addition to coffee packaging which is still very simple. Therefore, to overcome these problems in this service program, two activities were carried out, namely the first manufacture, training, and application of the solar dryer dome dryer. The existence of a solar dryer dome is expected to increase the quantity and quality of coffee production. The second is the creation, training, and marketing assistance with web marketplace-based applications and attractive coffee packaging. The application of an attractive marketplace and packaging is expected to help increase the marketing of coffee products.